Humoral and intestinal immunity induced by new schedules of bivalent oral poliovirus vaccine and one or two doses of inactivated poliovirus vaccine in Latin American infants: an open-label randomised controlled trial. Issue 10040 (9th July 2016) - Asturias, Edwin J; Bandyopadhyay, Ananda S; Self, Steve; Rivera, Luis; Saez-Llorens, Xavier; Lopez, Eduardo; Melgar, Mario; Gaensbauer, James T; Weldon, William C; Oberste, M Steven; Borate, Bhavesh R; Gast, Chris; et al.
Summary: Background: Replacement of the trivalent oral poliovirus vaccine (tOPV) with bivalent types 1 and 3 oral poliovirus vaccine (bOPV) and global introduction of inactivated poliovirus vaccine (IPV) are major steps in the polio endgame strategy. In this study, we assessed humoral and intestinal immunity in Latin American infants after three doses of bOPV combined with zero, one, or two doses of IPV. Methods: This open-label randomised controlled multicentre trial was part of a larger study. 6-week-old full-term infants due for their first polio vaccinations, who were healthy on physical examination, with no obvious medical conditions and no known chronic medical disorders, were enrolled from four investigational sites in Colombia, Dominican Republic, Guatemala, and Panama. The infants were randomly assigned by permuted block randomisation (through the use of a computer-generated list, block size 36) to nine groups, of which five will be discussed in this report. These five groups were randomly assigned 1:1:1:1 to four permutations of schedule: groups 1 and 2 (control groups) received bOPV at 6, 10, and 14 weeks; group 3 (also a control group, which did not count as a permutation) received tOPV at 6, 10, and 14 weeks; group 4 received bOPV plus one dose of IPV at 14 weeks; and group 5 received bOPV plus two doses of IPV at 14 and 36 weeks. Infants in all groups were challenged with monovalent type 2 vaccine (mOPV2) at 18 weeks (groups 1, 3, and 4) or 40 weeks (groups 2 and 5). The primary objective was to assess the superiority of bOPV–IPV schedules over bOPV alone, as assessed by the primary endpoints of humoral immunity (neutralising antibodies—ie, seroconversion) to all three serotypes and intestinal immunity (faecal viral shedding post-challenge) to serotype 2, analysed in the per-protocol population. Serious and medically important adverse events were monitored for up to 6 months after the study vaccination. This study is registered withClinicalTrials.gov, numberNCT01831050, and has been completed. Findings: Between May 20, 2013, and Aug 15, 2013, 940 eligible infants were enrolled and randomly assigned to the five treatment groups (210 to group 1, 210 to group 2, 100 to group 3, 210 to group 4, and 210 to group 5). One infant in group 1 was not vaccinated because their parents withdrew consent after enrolment and randomisation, so 939 infants actually received the vaccinations. Three doses of bOPV or tOPV elicited type 1 and 3 seroconversion rates of at least 97·7%. Type 2 seroconversion occurred in 19 of 198 infants (9·6%, 95% CI 6·2–14·5) in the bOPV-only groups, 86 of 88 (97·7%, 92·1–99·4) in the tOPV-only group (p<0·0001 vs bOPV-only), and 156 of 194 (80·4%, 74·3–85·4) infants in the bOPV–one dose of IPV group (p<0·0001 vs bOPV-only). A further 20 of 193 (10%) infants in the latter group seroconverted 1 week after mOPV2 challenge, resulting in around 98% of infants being seropositive against type 2. After a bOPV–two IPV schedule, all 193 infants (100%, 98·0–100; p<0·0001 vs bOPV-only) seroconverted to type 2. IPV induced small but significant decreases in a composite serotype 2 viral shedding index after mOPV2 challenge. 21 serious adverse events were reported in 20 patients during the study, including two that were judged to be possibly related to the vaccines. Most of the serious adverse events (18 [86%] of 21) and 24 (80%) of the 30 important medical events reported were infections and infestations. No deaths occurred during the study. Interpretation: bOPV provided humoral protection similar to tOPV against polio serotypes 1 and 3. After one or two IPV doses in addition to bOPV, 80% and 100% of infants seroconverted, respectively, and the vaccination induced a degree of intestinal immunity against type 2 poliovirus. Funding: Bill & Melinda Gates Foundation.